Efficiency in stock markets with DEA: evidence from PSI20 - Ferreira, N.; Souza, A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
After the US subprime crisis, the first signs of a sovereign debt crisis spread among European financial players. The regulation of the markets by European Commission and European Central Bank created limitation to obtained great amount of liquidity in commercial banking sector. In this context, the successful survival of some European banks became in a dangerous situation. The present study try to explore the crisis occurred in one of the largest private Portuguese banks through the analysis of the efficiency levels of twenty largest enterprises of the PSI20 since 1993. The input variables chosen were market value and return in a Data Envelopment Analysis model. Consistent with earlier studies, the results show substantial revenue inefficiencies among the Portuguese enterprises.